A Primary Analysis of the International Heath Regulation Implementation Within China and New Zealand COVID Measures - Fikri Fahmi Fahruqi (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2024)
This paper discusses an analysis of the legal framework of the 2005 International Health Regulations, specifically Article 43 in relation with the concept of “Additional Health Measures” and seeing how this Article, which currently lacks sufficient jurisprudence, is supposed to be applied within practice especially during pandemics such as COVID-19. The purpose of such is to form a guideline for States parties to this Regulation in its implementation, as is often seen within reality that there exists inconsistent application of it during pandemics, causing a considerable amount of its violation. Hence, because of the lack of jurisprudence for the Regulation, this paper will attempt to use a doctrinal method in interpreting the key terms of the Regulation, with additionally using other sources of law in support to find a meaning. It will be found later in the paper the usage of the 1994 World Trade Organization Sanitary and Phytosanitary Measures Agreement can be used to understand the technicalities of the Regulation as many of its terms were inspired by said agreement. After understanding the technicalities of Article 43, an assessment of its implementation will be done where we will find how countries like China, which has made restrictive health measures of the extreme, has violated the provision of the Regulation and how countries like New Zealand which has achieved its goal of reducing COVID cases by taking less restrictive measures, has complied with the Regulation.